Crystal structure of 5-hydroxy-3,5,8a-trimethyl-4a,5,6,7,8a,9-hexahydronaphtho[2,3-b]furan-4,8-dione, C15H18O4 - Wang Mei-Ling; Wu Jie; Cai Pan-Feng; Ye Jiang-Hai; Zou Juan; Li Qi-Ji; Liu Ya-Hua; Li Ji-Xin (Zeitschrift für Kristallographie - New Crystal Structures)
C15H18O4, triclinic, P1‾$P\overline{1}$ (no. 2), a = 6.7517(6) Å, b = 9.0117(8) Å, c = 11.5876(10) Å, α = 108.039(2), β = 100.136(2)°, γ = 90.748(2), V = 658.20(10) Å3, Z = 2, Rgt(F) = 0.0608, wRref(F2) = 0.1634, T = 273 K.